4v+3=-7(v+9)

Simple and best practice solution for 4v+3=-7(v+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4v+3=-7(v+9) equation:



4v+3=-7(v+9)
We move all terms to the left:
4v+3-(-7(v+9))=0
We calculate terms in parentheses: -(-7(v+9)), so:
-7(v+9)
We multiply parentheses
-7v-63
Back to the equation:
-(-7v-63)
We get rid of parentheses
4v+7v+63+3=0
We add all the numbers together, and all the variables
11v+66=0
We move all terms containing v to the left, all other terms to the right
11v=-66
v=-66/11
v=-6

See similar equations:

| -5e-50=10 | | -72-35=m | | 24=-7x+5(x+8) | | -1740q+847=-602-1830q | | 4^2-x=64 | | 5x+5-7500=237500 | | 4x+11=-29+6x | | 174x-12x^2=209+12x | | -9-12=p | | 4x+13=5x-8 | | 60/3x-1=30 | | c/7-7=3 | | -2.4=0.6-3y | | 2z+3=-z-18 | | g-4(2g+3)=2 | | 27-12=x | | -16+10c=-14+11c-18 | | 5x=29=4 | | 2(4x-1)=7x+1 | | 4–5x=29;5.00 | | 2(4x-1)=7x-1 | | -5(h-3)-2(-2+h)=26 | | 2(4c-1)-12=6c+2 | | 2c^2+4=4c | | -4p-6(6-2p)=6(p-4)-12 | | 6x-2=4x+36 | | -8(n+7)=-6 | | 11x-20=10x-15 | | 2(3x-10)+8=8x+12 | | -8.8j-8.35=-8.3j | | 3^(7x)=110 | | 2(6+3x)=27+33 |

Equations solver categories